Pendampingan Teknis Persiapan Dokumen Usulan Pembangunan Pagar Rumah Sewa di Gampong Meunasah Tutong Kecamatan Ingin Jaya, Kabupaten Aceh Besar - Faisal, Ruhdi; Suryani, Fitrika Mita; Abdullah, Nora; Mutiawati, Cut; Taufiq, Luthfi Chaliqi (PESARE: Jurnal Pengabdian Sains dan Rekayasa, 2025)
Gampong Meunasah Tutong is one of the villages in Ingin Jaya District, Aceh Besar Regency. Currently, the central government has a village fund program that is prioritized to finance development and community empowerment to improve community welfare. In 2023, Gampong Meunasah Tutong plans to build houses and fences for rental houses on land that is a Gampong asset. The house is expected to become a profitable asset for the Gampong in the future. The scope of activities carried out includes technical work such as preliminary surveys and land area measurements, house and fence designs, calculations of work volumes and calculations of cost requirements. At the end of this activity, it is expected to produce supporting documents for the Budget Estimate Plan (RAB) proposal to be submitted to the relevant agencies as a requirement for disbursement of funds. The process of preparing this RAB also involves the village assistance team as examiners of the conformity of the proposed budget with the required standards.